Brain Images, Babies, and Bathwater: Critiquing Critiques of Functional Neuroimaging - Farah, Martha J. (The Hastings Center report, 2014)
Since the mid-1980s, psychologists and neuroscientists have used brain imaging to test hypotheses about human thought processes and their neural instantiation. In just three decades, functional neuroimaging has been transformed from a crude clinical tool to a widely used research method for understanding the human brain and mind. Such rapidly achieved success is bound to evoke skepticism. A degree of skepticism toward new methods and ideas is both inevitable and useful in any field. It is especially valuable in a science as young as cognitive neuroscience and its even younger siblings, social and affective neuroscience. Healthy skepticism encourages us to check our assumptions, recognize the limitations of our methods, and proceed thoughtfully. Skepticism itself, however, also must be examined. In this article, I review the most commonly voiced criticisms of functional neuroimaging. In the spirit of healthy skepticism, I will critically examine these criticisms themselves. Each contains at least a kernel of truth, although I will argue that in some cases the kernel has been overextended in ways that are inaccurate or misleading.